Does a combination of ultrasound, MRI, and biochemical amniotic fluid analysis improve prenatal diagnosis of esophageal atresia?. (25th April 2014) - Garabedian, C.; Verpillat, P.; Czerkiewicz, I.; Langlois, C.; Muller, F.; Avni, F.; Bigot, J.; Sfeir, R.; Vaast, P.; Coulon, C.; Subtil, D.; Houfflin‐Debarge, V.
ABSTRACT Objective Prenatal diagnosis of esophageal atresia (EA) remains a challenge. Our objective was to evaluate the combination of sonography, magnetic resonance imaging (MRI), and amniotic fluid biochemical markers in prenatal diagnosis of EA. Study design A retrospective study of all cases with prenatal suspicion of EA from January 2008 to May 2013 in our regional reference center was carried out. Patients were included if all the three tests were performed. For each test, sensitivity (Se), specificity (Sp), positive predictive value (PPV), and negative predictive value (NPV) were evaluated. Each test was compared using Fisher's exact test. Results Fifteen patients were referred at a median gestational age of 28+5 weeks (24–36) for suspicion of EA on the basis of small or non‐visualized fetal stomach bubble and/or polyhydramnios. Se, Sp, PPV, and NPV for sonographic pouch sign/MRI/biochemical amniotic fluid were respectively 40/100/100/45.5%, 80/100/100/71.4%, and 90/60/81.8/75%. MRI was the best predictive test (p = 0.007). Conclusion In case of ultrasound prenatal suspicion of EA (with or without visualization of the pouch sign), an MRI at 30–32 weeks using fast imaging employing steady‐state acquisition should be proposed. Biochemical amniotic fluid may be helpful and should be evaluated in a larger study. © 2014 John Wiley & Sons, Ltd.